KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA SEKOLAH MELALUI MANAJEMEN BERBASIS SEKOLAH - Hernita, Rika (Graduate Program Magister Manajemen Pendidikan, 2018)
This research investigated headmaster’s strategy to develop school’ culture through School Based Management. It used a qualitative approach with case studies. Data were collected by using interviews, observation, and study of the documents/artifacts. Data validation was done through credibility, transferability, dependability, and confirmability. This results showed that headmaster’s strategy to develop school’ culture started from developing discipline culture.